1974
DOI: 10.1037/h0036339
|View full text |Cite
|
Sign up to set email alerts
|

Anagram solving as a function of word imagery.

Abstract: Two experiments are reported which examine the role of imagery in anagram solving. In Experiment I 5s attempted 12 anagrams constructed from nouns of high or low imagery value, with either no information, structural information, or semantic information as aids to solution. All words had a Thorndike-Lorge frequency value of 20 or more words per million, and other variables known to influence anagram solution time were controlled (word length, number of possible solutions, frequency of successive letter pairs, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

1977
1977
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
0
12
1
Order By: Relevance
“…While high imagery items were solved significantly faster in one experiment, this effect was not present at the 0.05 level in the two other experiments that they reported. Dewing and Hetherington (1974) found that high imagery solutions significantly facilitated anagram solving when solution word frequency, bigram frequency and associative meaningfulness (Noble, 1952) were controlled. This result was replicated with different materials and extra controls for bigram frequency and versatility (Solso et al 1973) factors by Stratton, Jacobus and Leonard (1975).…”
Section: Introductionmentioning
confidence: 99%
“…While high imagery items were solved significantly faster in one experiment, this effect was not present at the 0.05 level in the two other experiments that they reported. Dewing and Hetherington (1974) found that high imagery solutions significantly facilitated anagram solving when solution word frequency, bigram frequency and associative meaningfulness (Noble, 1952) were controlled. This result was replicated with different materials and extra controls for bigram frequency and versatility (Solso et al 1973) factors by Stratton, Jacobus and Leonard (1975).…”
Section: Introductionmentioning
confidence: 99%
“…Intergroup reliabilities were satisfactory on all attributes. Significant correlations were found with previous word lists and the intercorrelations between dimensions matched previous findings.Recent studies have found that high-solution word imagery facilitates anagram solving (Dewing & Hetherington, 1974;Jablonski & Mueller, 1972; Stratton, Jacobus, & Leonard, 1975). However, word imagery is correlated with other potentially important attributes, notably concreteness, meaningfulness, familiarity, and age-of-acquisition (Paivio, Yuille, & Madigan, 1968; Stratton, Jacobus, & Brinley, 1975).…”
mentioning
confidence: 99%
“…Previous research has shown that providing solvers with cues, in addition to the anagram itself, can aid the process of anagram solution. Both categorical cues (Dewing & Hetherington, 1974;Murray & Mastronardi, 1975;Schubert, Spoehr, & Haertal, 1979) and associative cues (Safren, 1962) have been shown to facilitate anagram solution. However, previous studies, using single-letter cues with shorter anagrams (Dominowski, 1968;Murray & Mastronardi, 1975), did not find such cues to facilitate the solution process.…”
Section: Discussionmentioning
confidence: 99%
“…Using 5-letter solution words, Dewing and Hetherington (1974) found that performance was facilitated if the first and last letter of the solution words were simultaneously presented. Murray and Mastronardi (1975), using solution words ranging from 3 to 9 letters, presented just the first letter of the solution word.…”
mentioning
confidence: 99%